Orteronel Switch Maintenance Therapy in Metastatic Castration Resistant Prostate Cancer After First‐Line Docetaxel: A Multicenter, Randomized, Double‐Blind, Placebo‐Controlled Trial (SAKK 08/11). Issue 16 (25th July 2016) - Cathomas, Richard; Crabb, Simon J.; Mark, Michael; Winterhalder, Ralph; Rothermundt, Christian; Elliott, Tony; von Burg, Philippe; Kenner, Heike; Hayoz, Stefanie; Vilei, Simona Berardi; Rauch, Daniel; Roggero, Enrico; et al.
Abstract : BACKGROUND: We tested whether a switch maintenance treatment with orteronel, an oral inhibitor of androgen biosynthesis, prolongs disease control in men with metastatic castration‐resistant prostate cancer (mCRPC) after documented disease stabilization with docetaxel. METHODS: Men with mCRPC and non‐progressive disease after a cumulative dose of ≥300 mg/m 2 docetaxel for first line treatment were randomized 1:1 to receive orteronel 300 mg twice daily or placebo. The primary endpoint was event‐free survival (EFS) defined as the time from randomization to death or the combination of at least two of radiographic, clinical, or PSA progression. Ninety‐six patients per arm were planned to demonstrate an improvement of median EFS from 4 months on placebo to 6.7 months on orteronel (hazard ratio (HR) 0.6; type I error 5% and power 90%). RESULTS: Forty‐seven patients (23 orteronel, 24 placebo) were randomized before premature closure of the trial because of discontinuation of clinical development of orteronel. Median EFS was 8.5 months with orteronel and 2.9 months with placebo ( P = 0.001; HR 0.32; 95%CI 0.15–0.65). Median radiographic progression‐free survival (rPFS) was 8.5 and 2.8 months ( P = 0.02; HR 0.42; 95%CI 0.20–0.91) in the orteronel and placebo arm, respectively. PSA decline ≥50% was seen in 57% on orteronel and 4% on placebo. Toxicity was mainly mild, one patient on orteronel developed transient grade 3 adrenal insufficiency and one grade 4 pneumonitis. CONCLUSIONS: Orteronel significantly prolongs EFS in men with mCRPC who achieve disease stabilization with docetaxel. The concept of switch maintenance therapy in mCRPC warrants further research. Prostate 76:1519–1527, 2016 . © 2016 Wiley Periodicals, Inc.